Experimental methods for the characterization of fatigue in microstructures - G. De Pasquale; A. Somà (Fracture and Structural Integrity, 2012)
The mechanical fatigue behavior of gold microbeams is analyzed. Dedicated devices have been designed and built able to produce alternate loading on gold specimens; the electrostatic actuation is used as driving force. Gold beams are tested under both bending and tensile alternate loadings. Results were used to plot S-N curves and fatigue Goodman-Smith diagram in order to estimate the fatigue limit of the material in presence of mean and alternate stress conditions. The surface topography evolution is studied and failure modes are discussed.